Comorbidities cluster with impaired functional capacities and depressive mood and predict adverse outcome in older patients with hematological malignancies. Issue 8 (2nd July 2020) - Nagl, Laurenz; Koinig, Karin; Hofer, Florian; Stauder, Reinhard
Abstract: This study evaluates prevalence of comorbidities and their association with impairments in older patients with hematological malignancies at initial diagnosis ( n = 209). At least one comorbidity was present in 62.2%, 68.5% and 93.8% as defined by CCI (Charlson Comorbidity Index), Cumulative Illness Rating Scale–Geriatric (CIRS-G) and HCT-Comorbidity Index, respectively. Severe comorbidities (CIRS-G Grade 3/4) were present in 57.9%. The mean number of affected organ systems was 3.6 (CIRS-G categories), with diabetes (18.2%), congestive heart failure and prior solid tumors (each 17.7%) detected most frequently. Comorbidities were significantly correlated with reduced functional and objective physical capacities, impaired performance and depressive mood. Both CCI and CIRS-G were found to be prognostic factors for OS ( p < 0.05). CCI scoring of comorbidities, diagnosis MDS/AML and a body mass index <23kg/m 2 were independent adverse predictors for OS. This first prospective analysis reveals a prognostic significance of comorbidities. Clustering of comorbidities with impairments suggests common mechanisms.